Russkii plakat : 100 shedevrov za 100 let = the Russian poster : 100 masterpieces during 100 years - sostavlenie: Snopkov Aleksandr Efimovich et al.. (Rossiiskaia gosudarstvennaia biblioteka ; "Kontakt-Kul'tura", 2001)
Includes indexes.